2014
DOI: 10.1080/13218719.2014.918078
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Question Type and Empathy on Police Interviews with Suspects of Homicide, Filicide and Child Sexual Abuse

Abstract: Conducting interviews with "high-stake" offenders, especially those accused of murder and sexual offences, represents a complex and emotive area of work for police officers. Using an English sample of 59 actual police interviews, the effects of empathy and question type on the amount of investigation-relevant information obtained from interviews with suspects of child murder, child sex offences and adult murder were analysed and compared. No direct effects of empathy on the amount of information elicited were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 40 publications
4
24
1
2
Order By: Relevance
“…The relationship between empathic interviewing style and admission has not been consistently demonstrated (Oxburgh, Ost, Morris, & Cherryman, 2014)-which could be due to methodological issues. Oxburgh et al (2014) identified empathic interviewer behaviour from written transcripts, rather than the reports of the interviewees (Holmberg & Christianson, 2002;Kebbell et al, 2006), which may have shaped their findings. Oxburgh et al noted that there are likely to be nonverbal elements of empathy that are not accessible from interview transcripts alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between empathic interviewing style and admission has not been consistently demonstrated (Oxburgh, Ost, Morris, & Cherryman, 2014)-which could be due to methodological issues. Oxburgh et al (2014) identified empathic interviewer behaviour from written transcripts, rather than the reports of the interviewees (Holmberg & Christianson, 2002;Kebbell et al, 2006), which may have shaped their findings. Oxburgh et al noted that there are likely to be nonverbal elements of empathy that are not accessible from interview transcripts alone.…”
mentioning
confidence: 99%
“…Conversely, "dominant" interviewing styles, where police officers were experienced as aggressive, brusque, impatient, and condemning, were associated with suspects maintaining their innocence. The relationship between empathic interviewing style and admission has not been consistently demonstrated (Oxburgh, Ost, Morris, & Cherryman, 2014)-which could be due to methodological issues. Oxburgh et al (2014) identified empathic interviewer behaviour from written transcripts, rather than the reports of the interviewees (Holmberg & Christianson, 2002;Kebbell et al, 2006), which may have shaped their findings.…”
mentioning
confidence: 99%
“…Despite the findings described above, the use of empathy in police interviews with suspects of sexual abuse has shown no direct effect on the amount of information elicited (Oxburgh & Ost, 2011;Oxburgh, Ost, Moris & Cherryman, 2014). However, empathy has been correlated with significantly more appropriate questions being asked, which in turn, elicited more information (Oxburgh et al, 2014). The same study additionally showed that suspects of CSA were asked significantly more inappropriate questions compared to suspects of child or adult murder.…”
mentioning
confidence: 81%
“…This can be further compounded where this role is in conflict with the wider goals and expectations of their organisation. These conflicting expectations can indeed have an impact on the progress of a prosecution as it has been demonstrated that while there is no direct link between empathy and the amount of investigation-relevant information obtained was found, there was evidence to suggest that more emphatic approaches to interviewing victims of abuse can lead to the adoption of more appropriate questions, and consequently, elicit more items of relevant information (Oxburgh et al 2014) . Making a child feel at ease and establishing rapport with the child prior to asking abuse -related questions is also critical (Hershkowitz et al, 2014).…”
Section: Child Protection Policing: Implications For Police Officersmentioning
confidence: 99%